2016
DOI: 10.1088/1475-7516/2016/12/009
|View full text |Cite
|
Sign up to set email alerts
|

Analytic study of the effect of dark energy-dark matter interaction on the growth of structures

Abstract: Abstract. Large-scale structure has been shown as a promising cosmic probe for distinguishing and constraining dark energy models. Using the growth index parametrization, we obtain an analytic formula for the growth rate of structures in a coupled dark energy model in which the exchange of energy-momentum is proportional to the dark energy density. We find that the evolution of f σ 8 can be determined analytically once we know the coupling, the dark energy equation of state, the present value of the dark energ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 106 publications
2
41
0
2
Order By: Relevance
“…Essentially these interacting models invoke energy exchange between the dark components and a small degree of momentum exchange. These scenarios have been intensively investigated in the literature for several dark sector coupling functions and observational approximations [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. It has recently been shown that the current observational data can favor the late time interaction between DE and DM [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Essentially these interacting models invoke energy exchange between the dark components and a small degree of momentum exchange. These scenarios have been intensively investigated in the literature for several dark sector coupling functions and observational approximations [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. It has recently been shown that the current observational data can favor the late time interaction between DE and DM [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…These baryon acoustic oscillations provide 6 See also Coc, Uzan & Vangioni [24] for more recent predictions of the light element abundances with the results by the Planck satellite mission. a standard ruler for the length scale of clustering of baryonic matter, which is about 150 Mpc today [32].…”
Section: Baryon Acoustic Oscillationsmentioning
confidence: 78%
“…We are now interested in seeing how the growth of structures is affected by the presence of interaction between dark energy and dark matter. The following study produced an interesting result from the theoretical point of view and has been submitted to the Journal of Cosmology and Astroparticle Physics for publication [6]. The fact that the evolution of the growth rate can be solved approximately in an analytic form,…”
Section: Chaptermentioning
confidence: 96%
See 2 more Smart Citations